Carbon and nitrogen pools in thermokarst-affected permafrost landscapes in Arctic Siberia - Fuchs, Matthias; Grosse, Guido; Strauss, Jens; Günther, Frank; Grigoriev, Mikhail N.; Maximov, Georgy M.; Hugelius, Gustaf (2017)
Ice rich Yedoma-dominated landscapes store considerable amounts of organic carbon (C) and nitrogen (N) and are vulnerable to degradation under climate warming. We investigate the C and N pools in two thermokarst-affected Yedoma landscapes – on Sobo-Sise Island and on Bykovsky Peninsula in the North of East Siberia. Soil cores up to three meters depth were collected along geomorphic gradients and analysed for organic C and N contents. A high vertical sampling density in the profiles allowed the calculation of C and N stocks for short soil column intervals and enhanced understanding of within-core parameter variability. Profile-level C and N stocks were scaled to the landscape level based on landform classifications from five-meter resolution, multispectral RapidEye satellite imagery. Mean landscape C and N storage in the first meter of soil for Sobo-Sise Island is estimated to be 20.2 kg C m−2 and 1.8 kg N m−2 and for Bykovsky Peninsula 25.9 kg C m−2 and 2.2 kg N m−2. Radiocarbon dating demonstrates the Holocene age of thermokarst basin deposits but also suggests the presence of thick Holocene aged cover layers which can reach up to two meters on top of intact Yedoma landforms. Reconstructed sedimentation rates of 0.10 mm yr−1–0.57 mm yr−1 suggest sustained mineral soil accumulation across all investigated landforms. Both Yedoma and thermokarst landforms are characterized by limited accumulation of organic soil layers (peat). We further estimate that an active layer deepening by about 100 cm will increase organic C availability in a seasonally thawed state in the two study areas by ~ 5.8 Tg (13.2 kg C m−2). Our study demonstrates the importance of increasing the number of C and N storage inventories in ice-rich Yedoma and thermokarst environments in order to account for high variability of permafrost and thermokarst environments in pan-permafrost soil C and N pool estimates.